Asia Pacific Regional integration index construction, interpretation, and comparison. (Economics working papers., 2017)
The index comprises 26 indicators in six dimensions of regional integration, i.e., trade and investment, money and finance, regional value chains, infrastructure and connectivity, free movement of people, and institutional and social integration. In constructing composite indexes, principal component analysis was used to determine the weight of each dimension and indicator. The resulting indexes help assess the state of regional integration on diverse socioeconomic dimensions, evaluate progress against goals, identify strengths and weaknesses, and track progress.